2019
DOI: 10.3390/su11154203
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quality Failures in Building Energy Renovation Projects in Northern China

Abstract: Building energy renovations contribute significantly to energy sustainability and environmental protection. These advantages have increased the importance of renovating existing residential buildings in many countries. In China, the government has supported the energy-saving renovation of existing urban residential buildings since 2007. However, quality failures, which do not meet the technical requirements, occur during construction processes in building energy renovation projects. Although quality failures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…On the other hand, too many selection criteria makes analysis difficult [17] for practitioners and consultants. Qi [18] showed that quality control during the renovation preparation stage is critical to ensure that quality failures are reduced in numbers and severity. In the changing climate conditions, it means that the market participants must find efficient ways to improve the quality of design and installation to meet increasing requirements of energy and hygrothermal performance of new and existing buildings.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, too many selection criteria makes analysis difficult [17] for practitioners and consultants. Qi [18] showed that quality control during the renovation preparation stage is critical to ensure that quality failures are reduced in numbers and severity. In the changing climate conditions, it means that the market participants must find efficient ways to improve the quality of design and installation to meet increasing requirements of energy and hygrothermal performance of new and existing buildings.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of energy renovation, three main constructive elements of the building are considered: Openings (doors and windows), roofs, and external walls. The work in [39,40] includes technical specifications linked to each of these elements: Actions related to the replacement of doors and windows consist in guaranteeing some values for the heat-transfer coefficient and the air ventilation rate; in the case of thermal insulation of roofs, control on the kind of material, bulk density, heat-transfer coefficient, thermal conductivity of the insulation, tensile/compressive strength and dimensional stability; finally, for the thermal insulation of exterior walls, similar actions to those of roof insulation are required, by checking the kind of material, bulk density, heat-transfer coefficient, thermal conductivity of the insulation, tensile/compressive strength and dimensional stability.…”
Section: Existing Pathology Databasesmentioning
confidence: 99%
“…Jha and Iyer [30] defined quality as "compliance with customer's specifications and customer's expectations". As defined by Qi et al [7], the definition of quality in construction projects is to meet the technical requirements of regulatory agencies.…”
Section: Quality and Quality Failuresmentioning
confidence: 99%
“…For example, doors, windows, roofs, and external walls are renovated. However, various quality failures have happened and resulted in construction repair and even rework [6,7]. Additionally, some quality failures were repeated in building energy renovation projects [8,9], which caused losses for stakeholders [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation